Optimizing thermal performance of evacuated tube solar collectors with cascaded phase change materials - Sana Said; Sofiene Mellouli; Talal Alqahtani; Salem Algarni; Ridha Ajjel; Badr M. Alshammari; Lioua Kolsi (Case Studies in Thermal Engineering)
This study assesses the performance of an Evacuated Tube Solar Collector (ETSC) featuring cascaded Phase Change Materials (PCMs). Numerical simulations are employed to conduct a comparative analysis of two new design configurations of the ETSC that utilize cascaded PCMs. Configuration 1 is an ETSC with stacked PCM rings, while Configuration 2 is an ETSC with surrounding PCM layers. Five different PCMs are evaluated to identify the best combination of cascaded PCMs for the ETSC. The impact of the cascaded PCMs' frequency and arrangement on the system's thermal efficiency is examined. A comparative analysis of cascaded configurations and single PCM cases in ETSCs is conducted. The findings suggest that PCM 3 (Rubitherm RT50) is the most suitable option for a standard ETSC utilizing a single PCM, achieving a maximum efficiency of 34.74 %. The optimal arrangement for Configuration 1, featuring three stacked PCM rings, achieves the highest overall efficiency of 36.73 % and an Energy Enhancement Ratio (EER) of 1.74 % compared to a standard ETSC. In contrast, the optimal arrangement for Configuration 2, which incorporates two surrounding PCM layers, reaches a maximum efficiency of 36.64 %. These results underscore the importance of PCM selection and arrangement in optimizing the performance of an ETSC that utilizes cascaded PCMs for improved energy storage and efficiency.